(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper, the task of design and implementation of digital pre-distortion technique has been divided into two parts. The behavioural model of power amplifier has been developed and digital predistorters module has been developed. AM-AM characterstics for the proposed model is presented and power spectral density (PSD) have been considered as the major parameters to check the performance and modelling accuracy. Parameter estimation and their automatic adjustment is a key issue in adaptive digital predistorter design.